PERGERAKAN SOSIAL: ANTARA MARXIAN DAN NON MARXIAN - Adi Prasetijo (Jurnal Antropologi: Isu-Isu Sosial Budaya, 2015)
Social movement always has seen as the negative term in the ruling class or authority standpoint. They perceive social movements as destructive action, and to weaken social stability. However, those who oppose the ruling class said that social movements are necessary action to against authority. In this paper will see how the theoretical debate between Marxian and non-Marxian, in looking at social movements.  This is including the role of intellectuals and the charismatic leaders; as well as ideological aspects ought to be discussed as part of a social movement theory paradigm debate.